Evaluation of varieties of common hop (Humulus lupulus L.) collection according to agronomic traits - Yu. S. Osipova; V. V. Leontieva; D. A. Dementiev (Аграрная наука Евро-Северо-Востока)
The paper presents the results of 2018-2020 research on the study of 248 Russian and foreign varieties of the collection of common hop (Humulus lupulus L.) in order to identify promising ones with a complex of agronomic traits for developing new varieties adapted to the natural and climatic conditions of the hop-growing regions of the Russian Federation. The research was carried out in the conditions of the Chuvash Republic on dark gray forest heavy loamy soil. Sixty hop varieties in the early-ripening, mid-early and mid-ripening groups with the yields above 26.3 c/ha (weighing more than 3.5 kg of raw cones from one bush) were identified. High-yielding varieties prevailed in the mid-ripening group of the collection (67 %). The adaptability of the collection varieties to natural and climatic conditions was evaluated on the third, fourth and fifth years of the hop plantings (in three tabs). There have been identified six varieties, which in some years of growing exceeded the control variety Podvyazny according to adaptability coefficients (1.23-1.23-1.15): early-ripening English variety Golden Star (1.58-1.37-1.03); mid-early Russian variety Zvenigovsky (1.72-1.16-1.07); mid-ripening Russian variety Serebryanka Kalistovskaya (1.47-1.28-1.17), Guslitsky (1.50-1.26-1.23), Ukrainian Kruglyak-Seryak (1.76-1.44-1.18), Group 4 (1.80-1.80-1.31). The most consistently high results were shown by Group 4, Guslitsky, Kruglyak-Seryak. High-resinous varieties with a high content of alpha acids belonging to different types of hops were noted specifically. According to the complex of agronomic traits and resistance to false powdery mildew, 19 collection varieties have been identified.